The good practice of inclusion in action - the proposal of program based on the Human Rights - Farnicka, Marzanna (Magyar Gerontológia, 2021)
Rapidly changing time is a problem: are we able to deal with all challenges in a humanistic and peaceful way? Is it possible? Do falling barriers to trade have led to a rapid change in social life and in the movement of products and labor? With these exciting transformations also came great challenges and threats, at a time when we seem to like each other less and less, with partisan affective polarization on the rise in a country after country. The paper presents definitions of phenomenon of marginalization and exclusion from European perspective. The main idea of its lecture and planned project is the presentation the intervention program among seniors based on heritage of work the French Research Committee on Violence, Crime and Delinquency, who published 40 years ago a document Society against Violence. The document contained analyses on the occurrence of social problems and their determinants, as well as guidelines to reduce risks and reduce the sense of threat and insecurity in modern society. Based on the conclusion included into Report “Society against Violence” the special training was prepared. The theoretical assumption of the project is Levinian model of changes in society and his methodology of action research. The aims of program are to change attitudes in the field of knowledge and attitudes towards the used violence and to improve the skills to react in situations of confrontation with institutional or press aggression or the so-called manifestations of "hate speech" in education institutions. Because of Coronavirus lockdown only idea and first step of implementation (the realisation was stopped) is possible to presentation. Maybe the program is in a primary stage but we believe that modern societies should relay and based on the idea of Human Rights and spread them elsewhere and that violence in modern societies should be reduced by human rights and democracy education. The document became the basis for the reflection on public debate on violence in international communities and psychological practice against violence in interpersonal and social meaning. The article presents the possible directions of research and psychological interventions in this area especially among seniors. This perspective is worth to be underlined because it is a part of wider trend in preparation social support programmes focused on inclusion adults from a difficult sociocultural environment. Such programmes could improve competencies to protect social capital of societies. The content and scope of these programmes should be drawn from knowledge of the relationships between the various risk factors, protective factors and developmental processes in groups and societies and combine knowledge, practical useful skills and good psychological experience by continue containing with life.